Interval and fuzzy eigenfrequency analysis of uncertain substructured FE models - De Gersem, Hilde; Moens, David; Desmet, Wim; Vandepitte, Dirk (Computer Assisted Methods in Engineering and Science, 2022)
This paper uses an interval and fuzzy finite element approach for the eigenfrequency analysis of a mechanical structure with uncertain parameters. The component mode synthesis method is applied for the numerical reduction of the structure, in order to reduce the calculation time of the interval and fuzzy analyses. Special attention is paid to the effect of uncertainties on the description of the substructuring technique and the consequences on the calculation time. All concepts are illustrated through a benchmark structure example.